The Effects of N-acetylcysteine on Transient Receptor Potential Melastatin 2 Channels Activation and Expression in Testicular Tissue of Diabetic Rats - Turk, Ahmet; Ulas, Mustafa; Karadag, Abdullah; Kocaman, Nevin; Onalan, Ebru; Kuloglu, Tuncay (Springernature, 2023)
Introduction: Diabetes mellitus (DM) is a common, chronic metabolic disease that has harmful effects on many diverse tissues, including the testis. One of the ways of tissue damage is the modification of transient receptor potential melastatin 2 (TRPM2) channels by increased reactive oxygen species (ROS). In our study for the first time, it was aimed to investigate TRPM2 channel activation in testicular tissues of diabetic rats induced by streptozotosin (STZ) and to examine the efficacy of N-acetylcysteine (NAC) treatment, which is an antioxidant. Methods: In our study, 28 Wistar albino male rats aged 8-10 weeks were used, and animals were divided into four groups: control group, NAC group, DM group, and DM + NAC group. The experimental phase was designed as eight weeks. The malondialdehyde (MDA) level, which is an indicator for lipid peroxidation due to oxidative stress, was measured by the spectrophotometric method. The Tunel assay was used to determine apoptosis on testicular tissue. TRPM2 immunoreactivity was determined by the avidin-biotinperoxidase complex method, and quantitative polymerase chain reaction (QPCR) was used to determine TRPM2 expression levels. Results: It was seen that MDA levels were significantly increased in the DM group and decreased after NAC treatment. Similarly, it was observed that apoptosis levels, which increased significantly in diabetic rats, decreased to the levels of the control group after treatment. It was seen that TRPM2 activation and expression levels were significantly decreased in the DM group. Conclusion: The results of this study show that NAC regulates TRPM2 activation in the testicular tissue of patients with diabetes and has tissue-protective properties.
Keywords: diabetes mellitus; n-acetyl cysteine; oxidative stress; stz; trpm2